2022
DOI: 10.1073/pnas.2116197119
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages evolve enhanced persistence to a mucosal surface

Abstract: The majority of viruses within the gut are obligate bacterial viruses known as bacteriophages (phages). Their bacteriotropism underscores the study of phage ecology in the gut, where they modulate and coevolve with gut bacterial communities. Traditionally, these ecological and evolutionary questions were investigated empirically via in vitro experimental evolution and, more recently, in vivo models were adopted to account for physiologically relevant conditions of the gut. Here, we probed beyond conventional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The mucus in the lungs of CF patients is hyper-concentrated and has a unique structure that favours bacterial colonization and, as also occurs in gut mucosa, the phages bind to the mucus. The mucus creates spatial refuges that favour the coexistence between phages and bacteria, which can explain the coevolution of both (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…The mucus in the lungs of CF patients is hyper-concentrated and has a unique structure that favours bacterial colonization and, as also occurs in gut mucosa, the phages bind to the mucus. The mucus creates spatial refuges that favour the coexistence between phages and bacteria, which can explain the coevolution of both (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…However, very limited studies have reported the phage-mucus interactions in the airway and the potential impacts of phage efficacy on respiratory bacterial infection. Recent evidence suggests that phages can bind to aspects of normal mucus that improve their bactericidal activity ( 11 ). However, little is known about how the CF mucus impacts phage functionality ( Figure 2 ).…”
Section: The Potential Impact Of Cf Mucus On Phage Therapymentioning
confidence: 99%
“…This binding increased the retention of T4 in the environment, allowing more interaction between phage and E. coli and serving as a critical regulator for phage-mediated bacterial lysis ( 132 ). Other work in non-respiratory research has shown that phages adhering to mucin have enhanced virulence toward bacteria ( 11 , 133 ), empowering the chances of phage encountering bacterial hosts and providing additional mucosal immunity protection. Almeida et al ( 133 ) demonstrated using a natural infection system that tailed phages with Ig-like domains in the phage capsids preferentially bind to mucin-containing agar.…”
Section: The Potential Impact Of Cf Mucus On Phage Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the comparatively high-density bacterial communities associated with the human gut 19,20 , mucosal layer of corals 21 , and other host environments is suggested to favor integrase encoding temperate phage, as opposed to obligately lytic phage [22][23][24] . Phage targeting bacteria adhered to gut mucosa have also been shown to evolve the ability to adhere to and persist in the animal mucosa where their target bacteria reside 25 . Given the fundamental differences in the ecology of free-living and hostassociated phage communities 22 , it remains unclear whether sampling methods developed for free-living communities are also appropriate for other habitat types.…”
Section: Introductionmentioning
confidence: 99%